Loan supply shocks and the business cycle - Luca Gambetti; Alberto Musso (European Central Bank (ECB), 2012)
This paper provides empirical evidence on the role played by loan supply shocks over the business cycle in the Euro Area, the United Kingdom and the United States from 1980 to 2010 by applying a time-varying parameters VAR model with stochastic volatility and identifying these shocks with sign restrictions. The evidence suggests that loan supply shocks appear to have a significant effect on economic activity and credit market variables, but to some extent also inflation, in all three economic areas. Moreover, we report evidence that the short-term impact of these shocks on real GDP and loan volumes appears to have increased in all three economic areas over the past few years. The results of the analysis also suggest that the impact of loan supply shocks seems to be particularly important during slowdowns in economic activity. As regards to the most recent recession, we find that the contribution of these shocks can explain about one half of the decline in annual real GDP growth during 2008 and 2009 in the Euro Area and the United States and possibly about three fourths of that observed in the United Kingdom. Finally, the contribution of loan supply shocks to the decline in the annual growth rate of loans observed from the peaks of 2007 to the troughs of 2009/2010 was slightly less than half of the total decline in the Euro Area and the United States and somewhat more than half of that in the United Kingdom.
Keywords: C32; E32; E51; 330; business cycle; euro area; Loan supply; sign restrictions; time-varying VAR; UK; US